First record of fig bark beetle Hypoborus ficus Erichson (Curculionidae: Scolytinae) from Poland - Witkowski, Radosław; Mazur, Andrzej (Zootaxa, 2019)
Hypoborus ficus Erichson, 1836, is a widespread bark beetle in the Mediterranean region (Talhouk 1969). The species was recorded in Europe: Austria, Azerbaijan, Azores, Bosnia and Herzegovina, Bulgaria, Croatia, Cyprus, France (including Corsica), Greece, Hungary, Italy (including Sardinia and Sicily), Macedonia, Malta, Portugal, Southern Russia, Slovenia, Spain, Switzerland, Ukraine (Crimea); Africa: Algeria, Canary Islands, Egypt, Madeira Islands, Morocco, Tunisia; and Asia: Cyprus, Georgia, Iran, Iraq, Israel, Jordan, Syria, Tajikistan, and Turkey (Fontana 1925; Knížek 2011).